The Y3+ Donor-Doped CCTO (Ca0.95Y0.05Cu3Ti4O12) Dielectric Fillers for Electrical Output Enhancement of Flexible Triboelectric Nanogenerator - Saichompoo, Kittipan; Rattanawongwiboon, Thitirat; Kingkam, Wilasinee; Pakawanit, Phakkhananan; Sukkha, Usa; Onoda, Hiroaki; Hajra, Sugato; Khanapuram, Uday Kumar; Charoonsuk, Thitirat; Vittayakorn, Naratip (My University, 2026)
The escalating wearable electronic devices with their flexible energy sources demand has rendered the imperative scientific challenge on the development of materials for the flexible triboelectric nanogenerators (F-TENG), one of advanced energy harvesting systems. Dielectric material optimization, the Y3+ donor-doped calcium copper titanate based on exactly stoichiometric Ca0.95Y0.05Cu3Ti4O12 (CCTYO), serves as a critical pathway in this work for achieving enhanced F-TENG via compositing with the polydimethylsiloxane (PDMS) polymer. The enhancement of electrical output has garnered substantial interest owing to its increased relative permittivity ((Formula presented.)). The influence of the loaded CCTYO amounts on structure, morphologies, dielectric properties, and electrical output, including open-circuit voltage (VOC), short-circuit current (ISC) and power density for PDMS/CCTYO composites is investigated. As compared with loading undoped CCTO, the additional Y3+ can improve higher F-TENG output by increasing the (Formula presented.) along with maintaining the loss tangent (tan δ < 0.02) at optimized condition. The appropriate amounts of CCTYO 0.75 wt% make the PDMS/CCTYO F-TENG to achieve VOC of ∼76.4 V (8.5 V/cm2) and ISC of ∼130.0 μA (14.4 μA/cm2), which were higher than pristine PDMS for 2.7 and 4.3 times. The power density of 53 µW/cm2 is 8.9 times higher than that of 6.3 µW/cm2 from the pristine PDMS. This study also provides a COMSOL multiphysics simulation, bridging laboratory experiments, for quantifying the triboelectric capability of dielectric materials.
Keywords: calcium copper titanate; CCTO; donor-doped CCTO; flexible triboelectric nanogenerator; polydimethylsiloxane (PDMS)